Syntheses, structures, luminescence and magnetic properties of eleven coordination polymers constructed by a N, N′-sulfuryldiimidazole ligand1. Issue 27 (21st July 2015) - Liu, Kang; Ma, Benhua; Guo, Xiaolei; Ma, Dingxuan; Meng, Lingkun; Zeng, Guang; Yang, Fen; Li, Guanghua; Shi, Zhan; Feng, Shouhua
<x xml:space="preserve">Abstract</x> We report here eleven novel coordination polymers using the sdi ligand. These coordination polymers show rich structural chemistry ranging from 0D to 3D networks.